'Living things': metaphor and urban youth culture in Abolore Akande Adigun's (9ice) hip hop music. Issue 1 (2nd January 2023) - Ajayi, Daniel Oluwafemi
ABSTRACT: Unarguably, hip hop has a wide acceptance among Nigerians. One of the obvious reasons for this is its fusion with some aspects of indigenous cultures and experiences. Despite the existence of several scholarly engagements on linguistic and identity formations in hip hop in Nigeria, there is however a need to further explore how the emerging urban youth lifestyles are coded in hip hop metaphor. Hence, in this paper, I focus on the music of Abolore Akande (9ice) and his use of metaphors to discuss urban lifestyles in the Nigerian social space. Through a qualitative analysis of his song texts, using Lakoff and Johnson's conceptual metaphor theory, I argue that these metaphors and their conceptual domains are discursive paradigms through which certain notions about sex, gender, social status and crime in contemporary Nigeria can be graphically visualized and understood. I conclude that rather than regarding them as meaningless, unmotivated or bare linguistic practices instantiated only for aesthetic consumption, metaphors in Naija hip hop are significant in grounding and projecting the thriving urban social realities in Nigeria.